Challenges of entrepreneurial journalism in Mexico: comparing cases in the states of Jalisco and Chiapas - Noel Ramos Rojas, Diego; Martínez Mendoza, Sarelly (Brazilian journalism research, 2022)
ABSTRACT – Entrepreneurial journalism, which has multiplied in different parts of the world, has its own nuances in each country. In this paper we analyze eight journalistic projects in two states of Mexico, Chiapas and Jalisco; the first, the poorest in the country and with less access to the internet, and the second, of the most developed in the economic plane, with more teledensity and greater contribution to the national GDP. The results show, in both entities, enterprising journalistic projects not yet consolidated that explore different forms of revenue, such as institutional advertising agreements, first, and more marginally, commercial advertising, digital monetization, and solidarity support from readers and foundations. In Chiapas, the projects are characterized by being unipersonal initiatives, while in Jalisco they arise within the new cooperativism that digital journalism experiences. RESUMO – O jornalismo empreendedor, que se multiplicou em diferentes partes do mundo, apresenta suas próprias nuances em cada país. Neste trabalho analisamos oito projetos jornalísticos de dois estados do México, Chiapas e Jalisco; o primeiro, o mais pobre do país e de menor acesso à internet, e o segundo, dos mais desenvolvidos no plano econômico, com mais teledensidade e maior contribuição ao PIB nacional. Os resultados obtidos em ambas as entidades são projetos jornalísticos empreendedores ainda não consolidados que exploram diferentes formas de receitas, como convenções publicitárias institucionais, em primeiro lugar, e de forma mais marginal, publicidade comercial, monetização digital, e apoio solidário de leitores e de fundações. Em Chiapas, os projetos se caracterizam por serem iniciativas unipessoais, enquanto em Jalisco surgem dentro do novo cooperativismo que experimenta o jornalismo digital. RESUMEN – El periodismo emprendedor, que se ha multiplicado en diferentes partes del mundo, presenta sus propios matices en cada país. En este trabajo analizamos ocho proyectos periodísticos de dos estados de México, Chiapas y Jalisco; el primero, el más pobre del país y de menor acceso a internet, y el segundo, de los más desarrollados en el plano económico, con más teledensidad y mayor aportación al PIB nacional. Los resultados arrojan, en ambas entidades, proyectos periodísticos emprendedores aún no consolidados que exploran diferentes formas de ingresos, como convenios publicitarios institucionales, en primer lugar, y de manera más marginal, publicidad comercial, monetización digital, y apoyo solidario de lectores y de fundaciones. En Chiapas, los proyectos se caracterizan por ser iniciativas unipersonales, mientras que en Jalisco surgen dentro del nuevo cooperativismo que experimenta el periodismo digital.